PENGGUNAAN MARKETING MIXED 7P SEBAGAI DASAR CLUSTERING KOS – KOSAN PADA USAHA SEWA KAMAR KOSAN DI KECAMATAN SUMBERSARI JEMBER - Windra, Ayu Dita (Growth, 2025)
Research with the title “Marketing Mixed 7 P as a Basis for Clustering Kos - Kosan in the Kosan Room Rental Business in Sumbersari District Jember” aims to find out the grouping or clusters that are divided in the Sumbersari District Area of Jember Regency and identify the main groupings of boarding house clusters. Service marketing mix or better known as 7P is an independent variable in this study. The research design was carried out quantitatively and descriptively with SPSS data processing tools. Based on the results of data processing, 5 Kosan Clusters were obtained in Sumbersari Jember and the main consumer pattern centered on consumers who chose boarding houses based on needs being the main point of boarding house selection.